2007
DOI: 10.1128/aem.01893-06
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Pathogenic Biofilms to Micavibrio aeruginosavorus

Abstract: The host specificity of the gram-negative exoparasitic predatory bacterium Micavibrio aeruginosavorus was examined. M. aeruginosavorus preyed on Pseudomonas aeruginosa, as previously reported, as well as Burkholderia cepacia, Klebsiella pneumoniae, and numerous clinical isolates of these species. In a static assay, a reduction in biofilm biomass was observed as early as 3 hours after exposure to M. aeruginosavorus, and an ϳ100-fold reduction in biofilm cell viability was detected following a 24-h exposure to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 46 publications
6
79
2
1
Order By: Relevance
“…Similarly, in Pseudomonas aeruginosa, depolymerase enzyme reduced the viscosity of alginates and the EPS of the organism, thereby leading to dispersal of biofilm.The dual approach of impregnation of medical devices with phages and incorporation of phages in hydrogel coating of catheter has proven its efficacy, especially in Staphylococcus epidermidis (Del Pozo et al, 2007). The vulnerability of pathogenic biofilms to Micavibrio aeruginosavorus and Bdellovibrio bacteriovorus attack has been documented (Kadouri et al, 2007). However, recent studies have shown the dispersal of films by using genetically engineered bacteriophages (Lu and Collins, 2007).…”
Section: Approaches For Biofilm Control and Preventionmentioning
confidence: 99%
“…Similarly, in Pseudomonas aeruginosa, depolymerase enzyme reduced the viscosity of alginates and the EPS of the organism, thereby leading to dispersal of biofilm.The dual approach of impregnation of medical devices with phages and incorporation of phages in hydrogel coating of catheter has proven its efficacy, especially in Staphylococcus epidermidis (Del Pozo et al, 2007). The vulnerability of pathogenic biofilms to Micavibrio aeruginosavorus and Bdellovibrio bacteriovorus attack has been documented (Kadouri et al, 2007). However, recent studies have shown the dispersal of films by using genetically engineered bacteriophages (Lu and Collins, 2007).…”
Section: Approaches For Biofilm Control and Preventionmentioning
confidence: 99%
“…They are gram negative, small curved rod shaped (0.5 x 1.5 mm), bacteria with a single polar flagellum. A titer as low as 10 plaque forming units per well of M. aeruginosavorus was sufficient to produce a 78% reduction in a P. aeruginosa biofilm after 30 min exposure in a static assay (Kadouri et al, 2007). Dopheide et al (2011) examined the grazing interactions of two ciliates, the free-swimming filter feeder Tetrahymena spp.…”
Section: Predationmentioning
confidence: 99%
“…Micavibrio, on the other hand, feed by "leeching" externally to the surface of the prey cell and therefore has an epibiotic lifestyle (Lambina, et al 1983;Davidov, et al 2006;Kadouri, et al 2007;Dashiff, et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Micavibrio usually exhibit a high degree of prey specificity. For example, M. aeruginosavorus was initially reported to prey only on Pseudomonas aeruginosa, Burkholderia cepacia and Klebsiella pneumoniae (Lambina, et al 1983;Kadouri, et al 2007). However a breach in prey specificity was recently demonstrated and M. aeruginosavorus was found to be able to prey on many other bacterial species including…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation